2022
DOI: 10.3389/fonc.2022.888276
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs Implicated in the Tumor Microenvironment of Colorectal Cancer: Roles, Mechanisms and Clinical Study

Abstract: Colorectal cancer (CRC) is one of the most common malignant tumors. The morbidity and mortality rates have been increasing all over the world. It is critical to elucidate the mechanism of CRC occurrence and development. However, tumor microenvironment (TME) includes immune cells, fibroblasts, endothelial cells, cytokines, chemokines and other components that affect the progression of CRC and patients’ prognosis. Non-coding RNAs (ncRNAs) including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), circular RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 157 publications
0
0
0
Order By: Relevance
“…In colorectal cancer, it was reported that the tumor suppressor miR-195-5p promotes TAM polarization by suppressing NOTCH2 expression [85]. Furthermore, exosomal miRNAs (e.g., miR-934, miR-25-3p, miR-130b-3p, miR-425-5p) can induce the activation of the CXCL13/CXCR5 or CXCL12/CXCR4 axis in colorectal cancer cells, which in turn activate TAM polarization and metastasis to liver [86]. On the other hand, lncRNAs such as lnc-EGFR, SNHG1, Flicr, and Flatr can orchestrate the correct function and differentiation of Treg cells [86].…”
Section: Ncrnas and Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…In colorectal cancer, it was reported that the tumor suppressor miR-195-5p promotes TAM polarization by suppressing NOTCH2 expression [85]. Furthermore, exosomal miRNAs (e.g., miR-934, miR-25-3p, miR-130b-3p, miR-425-5p) can induce the activation of the CXCL13/CXCR5 or CXCL12/CXCR4 axis in colorectal cancer cells, which in turn activate TAM polarization and metastasis to liver [86]. On the other hand, lncRNAs such as lnc-EGFR, SNHG1, Flicr, and Flatr can orchestrate the correct function and differentiation of Treg cells [86].…”
Section: Ncrnas and Immune Responsementioning
confidence: 99%
“…Furthermore, exosomal miRNAs (e.g., miR-934, miR-25-3p, miR-130b-3p, miR-425-5p) can induce the activation of the CXCL13/CXCR5 or CXCL12/CXCR4 axis in colorectal cancer cells, which in turn activate TAM polarization and metastasis to liver [86]. On the other hand, lncRNAs such as lnc-EGFR, SNHG1, Flicr, and Flatr can orchestrate the correct function and differentiation of Treg cells [86]. Moreover, lnc-EGFR has also been shown to stimulate Treg differentiation, inhibit cytotoxic T lymphocyte activity, and induce hepatocellular carcinoma (HCC) growth [87].…”
Section: Ncrnas and Immune Responsementioning
confidence: 99%
“…In colorectal cancer, it was reported that tumor suppressor miR-195-5p promotes TAM polarization by the suppression of NOTCH2 expression (30). Furthermore, the exosomal miRNAs (miR-934, miR-25-3p, miR-130b-3p, miR-425-5p) can induce the activation of the CXCL13/CXCR5 or CXCL12/CXCR4 axis in colorectal cancer cells, which in turn activate TAM polarization and metastasis to liver (31). On the other hand, lncRNAs such as lnc-EGFR, lncRNA SNHG1, Flicr, and Flatr can orchestrate the correct function and differentiation of Tregs (31).…”
Section: Overview Of Tumor Immunitymentioning
confidence: 99%
“…Furthermore, the exosomal miRNAs (miR-934, miR-25-3p, miR-130b-3p, miR-425-5p) can induce the activation of the CXCL13/CXCR5 or CXCL12/CXCR4 axis in colorectal cancer cells, which in turn activate TAM polarization and metastasis to liver (31). On the other hand, lncRNAs such as lnc-EGFR, lncRNA SNHG1, Flicr, and Flatr can orchestrate the correct function and differentiation of Tregs (31). Moreover, lnc-EGFR has also been shown to stimulate Treg differentiation, inhibit cytotoxic T lymphocyte activity, and induce hepatocellular carcinoma (HCC) growth (32).…”
Section: Overview Of Tumor Immunitymentioning
confidence: 99%